THE WESTERN LEGAL SYSTEM IN INDONESIAN CRIMINAL PROCEDURAL LAW REFORM: A GLOBALIZATION AND LEGAL POLITICS PERSPECTIVE - Santoso, Bambang; Hartiwiningsih, Hartiwiningsih; Rustamaji, Muhammad (Jurnal Pembaharuan Hukum, 2024)
In the field of law, the influence of globalization is reflected in the legal politics of procedural law reform, which is currently still in the form of legislation draft. This study aims to analyze the influence of globalization on the reform of Indonesian criminal procedural law in relation to national legal politics. This research is normative legal research, which focuses on studying library materials. Based on the results of a comprehensive study is known, the Draft Criminal Procedure Code includes a new system originating from the western legal system such as adversary system in court trial. Adopting the adversary system into the Draft Criminal Procedure Code is a very revolutionary legal political reform of the criminal procedural law. Various challenges will be faced along with the adoption of the new legal system.  Changes in the legal culture of law bearers is also a key variable in the success or failure of a western legal system implementation. Although the concept of the Criminal Procedure Code is colored by the western legal system, it does not conflict with national legal politics because it reflects universal legal principles, namely equality.